Multiliteracies in local curricula: conceptual contextualizations of transversal competence in the finnish curricular framework - Lauri Palsa; Pekka Mertala (Taylor & Francis Group, 2019)
The international trend of competency-based curricula is evident in the curricular framework in Finland. In the latest effort of curricular reform, seven transversal competencies were introduced to the Finnish educational system. In this article, we analyse the ways in which multiliteracy as a transversal competency, presented in the Core Curriculum for Basic Education in Finland (2014), has been conceptually contextualized in local curricula. The study revealed that in most local curricula, the definition of multiliteracy was not contextualized within local settings. For the curricula in which contextualizations took place, most conceptual contextualizations focused on the level of practice (85%), level of definition (63%) and level of rationale (21%). Conceptual contextualizations were made through emphases, specifications, descriptions and expansions. The article contributes by highlighting the ways in which broadly defined competencies can be contextualized to local settings, offering new knowledge among growing extant literature on competency-based curricula. In addition to the contextualization process, the present study offers new insights into the ways in which the concept of multiliteracy can be understood.